Effect of Micronutrient Seed Treatments on Nutrient Uptake by Bt Cotton in Vertisol - Kale, A. S.; Patil, V. D.; Garde, A. P. (International Journal of Economic Plants, 2024)
The present investigation was carried out during the year June 2017 to January 2018 at Department of Soil Science and Agricultural Chemistry, College of Agriculture, Vasantrao Naik Marathwada Krishi Vidyapeeth, Parbhani, Maharashtra, India to study the effect of nutrient seed treatments on nutrient uptake, quality of Bt cotton and soil nutrient dynamics in vertisol. The field experiment was undertaken in a Randomized Block Design with nine treatments and three replications. The nutrient seed dressing treatments are absolute control, 100% NPK+Zinc Sulphate (ZnSo4), 100% NPK+Zn EDTA, 100% NPK+Borax (B), 100% NPK+Manganese Sulphate (MnSo4), 100% NPK+Sodium Molybdate (NaMo), 100% NPK+Copper Nitrate (CuNo3), 100% NPK+Ferrous Sulphate (FeSo4), 100% NPK+Fe EDTA seed application to Bt cotton. The maximum N, P, K, Fe, Mn, Zn, Cu, B and Mo uptake was recorded in the treatment 100 % NPK+Zn EDTA followed by 100% NPK+Fe EDTA treatment. In case of Mo uptake, the treatment 100 % NPK+Zn EDTA was significantly superior overall treatments except treatment 100% NPK+Fe EDTA and 100% NPK+Sodium Molybdate (NaMo). The minimum N, P, K, Fe, Mn, Zn, Cu, B and Mo uptake was recorded in the treatment Absolute control+100% NPK.